The Relationship between Health Literacy, Perceived Self-efficacy and Self-care Performance of Female Senior High School Students in Health Promoting Schools of Miyaneh, 2016-2017 - Mahnaz Khodabandeh; Sadegh Maleki Avarasin; Leila Nikniaz (Mashhad University of Medical Sciences, 2017)
Background and objective: Self-care in adolescents is considered as an effective measure in line with the promotion of health in each community. In this regard, the role of health promoting schools is of great importance. Furthermore, health literacy, as one of the basic tools for promoting community health, has been given much attention by policymakers. The present study aimed to investigate the relationship between the health literacy, perceived self-efficacy and self-care performance of female senior high school students in the health promoting schools of Miyaneh in 2016-2017. Methods:In this descriptive-correlational study, 320 female senior high school students were selected randomly using the multi -stage cluster sampling method. Data were collected by using the questionnaires of Health Literacy Measure for Adolescents (HELMA), General Self-efficacy Scale, and the Adolescent Health Promotion (AHP) scale. Data were analyzed by SPSS software (version 21) using the statistical tests of Pearson correlation coefficient and Multiple Regression (ENTER method). Results: The results showed that there is a positive and significant relationship between the health literacy and perceived self-efficacy and the self-care performance of female students in the health promoting schools, as well as between the components of health literacy and self-care components. No significant relationship was found between the component of health literacy calculation and the self-care components of nutrition, responsibility for health, spiritual growth, and physical activity. The results of regression analysis indicated that the dimensions of self-efficacy, use and correlation of health literacy are good predictors of self-care performance (R2 = 0.605). Moreover, the health literacy and the perceived self-efficacy can predict the self-care performance of students by 51 percent. Conclusion: The results of the present study indicated that a student with high levels of health literacy and the perceived self-efficacy has better self-care performance. Therefore, in order to improve the self-care performance of students, it is recommended that their health literacy and self-efficacy be improved at schools. Paper Type:Research Article.